Magnetic leakage field and losses in transformer winding : Specialist’s thesis = Rasipno polje i dodatni gubici u namotu transformatora : specijalistički rad - Kovač, Aleksander 1983. (A. Kovač ; Fakultet elektrotehnike i računarstva, 2012)
The aim of this thesis is to examine computationally efficient methods for loss analysis in transformer windings. The focus is on power transformers and on proximity or eddy current losses at low frequencies. Two 2D methods for eddy current loss calculation are analyzed, and a third 2D method is derived which combines the most important features of the other two methods. In addition, the derived method is extended to enable detailed 3D calculations. Explanations of the differences between 2D and 3D analysis are given. The accuracy of the derived 2D method is evaluated by comparing it with the detailed FEM simulation in two 2D cases with resulting relative differences of 1 % or less. The reasons for discrepancies and the method’s limitations are analyzed. To depict the differences between 2D and 3D analysis, a realistic power transformer 3D case is used. For the conclusion, the derived method and the eddy current losses are assessed in terms of the winding hot spot, and the differences between 2D and 3D analysis of the latter are examined. -